What is the impact of physician communication and patient understanding in the management of headache? - Meenal Patwardhan (Dove Medical Press, 2007)
Meenal Patwardhan1, Remy R Coeytaux2, Rajeshwari Deshmukh3, Gregory Samsa41Department of Medicine, Duke University Medical Center, Durham, NC, USA; 2Department of Family Medicine, University of North Carolina, Chapel Hill, NC, USA; 3Department of Rheumatology, Oregon Health Sciences University, Portland, OR, USA; 4Department of Biostatistics and Bioinformatics, Duke University, Durham NC, USAAbstract: Migraine is a common and debilitating condition. Despite the burden of disease and increasing availability of effective treatment, migraine management is unsatisfactory. Evidence in other chronic conditions indicates that effective physician communication results in better patient understanding and health outcomes.The current literature review was intended to evaluate evidence regarding the relationship of effective physician-provider communication to health outcomes and patient satisfaction among patients with migraine. The authors searched MEDLINE® (1966–June 2007) and the Cochrane Database of Systematic Reviews for relevant publications. The search strategy combined the concepts of “headache disorders” and “physician-patient relations”. 912 abstracts were identiified, and 80 (9%) of them were included for data abstraction.There were no studies that met our eligibility criteria. Therefore we revised the eligibility criteria to allow for the inclusion of non-migraine primary headache disorders or the role of non-physician health care providers. Twelve published papers met the revised criteria. The findings from the limited evidence available suggests, but does not prove, that improvements in physician-patient communication could result in a significant decrease in the burden of suffering and health care resource utilization associated with migraine. More research is needed to assess the explicit role of physician-patient communication in the management of migraine.Keywords: communication, migraine, headache, outcomes, physician communication, patient understanding